Foreign historiography on the position of women in Anglo-Saxon society of the 7th – 11th centuries - Boldyreva, Irina I. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2024)
The article focuses on foreign historiography devoted to the place and role of women in Anglo-Saxon society of the 7th – 11th centuries. Based on a review of the main academic publications, three successive periods are identified: the end of the 19th – 1st half of the 20th cc. – the beginning of the study of early medieval English women as subjects of history; 1950–1980s – the beginning of systematic research in this area; the turn of the 1980–1990s to our days – a significant increase in the number of publications due to the wide use of gender methodology. While in the second period medievalists demonstrated the importance of women in Anglo-Saxon society, historians of subsequent generations sought to emphasize their suppression. It is shown that despite the extensive number of special works, in modern medieval studies there is no holistic understanding of the position of women in early medieval England.